Research progress of treatment strategies for osteoradionecrosis of the jaws - WANG Xirui, ZHU Huiyong (Editorial Office of Stomatology, 2024)
Head and neck cancer is the seventh most common cancer in the world, accounting for about 10% of all malignant tumors. Radiotherapy is an important treatment for head and neck cancer. Osteonecrosis of the jaws(ORNJ) is a refractory complication after radiotherapy for head and neck cancer, which often manifests as osteonecrosis of the jaw and soft tissue exposure. The current pathogenesis of ORNJ has not been fully clarified and its treatment remains challenging. The traditional treatment for this disease is partial resection of necrotic jaw bone and reconstruction with osteocutaneous flap. However, in recent years, some new techniques and ideas have been used to treat the disease. For mild osteoradionecrosis of the jaw, the treatment concept tends to be conservative. This article mainly summarizes the latest research progress at home and abroad, and reviews the pathogenesis, clinical manifestations and treatment strategies for osteoradionecrosis of the jaws.